Variantes genéticas y niveles séricos de la ApoA1 y ApoB100 en gestantes peruanas con preeclampsia severa - Pacheco Romero, José (2024)
Background: Preeclampsia is a multi-organ disease that causes maternal and perinatalmorbidity and mortality, with an unclear pathophysiology and without specificprevention methods and/or treatments. Objective: To establish the associationbetween variants -75 G/A in the ApoA1 gene, 2488 C/T in the ApoB100 gene, serumlevels of ApoA1 and ApoB100 and severe preeclampsia in Peruvian pregnantwomen. Methods: Blood samples from pregnant women with severe preeclampsiaand healthy women (controls) were processed for DNA extraction and genotypingwith the PCR-RFLP technique. In addition, serum was analyzed to quantify ApoA1 andApoB100. Genotypes and alleles were compared between cases and controls, as wellas serum ApoA1 and ApoB100 levels considering genotypes. Results: No significantdifferences were found between the genotypic and allele frequencies of the -75 G/Avariant in the ApoA1 gene and 2488 C/T in the ApoB100 gene of both groups. Asignificant difference (p=0.039) was found when comparing serum ApoA1 in patientswith heterozygous GA genotypes, with lower average levels in severe preeclamptic(161.37 ± 40.21) compared to controls (185.37 ± 35.38). Conclusions: Although noassociation was found between the variants -75 G/A variants in the APOA1 gene and2488 C/T in the ApoB100 gene and preeclampsia, however, serum ApoA1 levels weresignificantly lower in severe preeclamptic women with GA heterozygous genotypethan in controls. Thus, we contribute to the understanding of preeclampsia inPeruvian pregnant women.